The Role of Education in Enhancing the Value of Citizenship in Children through the Interactive Life Process in Educational Institutions (Journal Of Educational and Psychological Researches, 2022)
The aim of the research is to diagnose the methods of enhancing the value of citizenship in children through the interactive life process in educational institutions; the descriptive approach was used to achieve the objective by identifying social theories that corresponded to the national value or the theoretical principles of citizenship education. The study focused on educational activities and their role in establishing values, national educational philosophy in interactive activities, as well as the presentation of previous studies on the subject of citizenship, and maps of each of the strategies of active learning, skills in the process of interactive life in the field of education, Institutions that have the responsibility to promote national identity have also been identified, Such as the media and the school.The researcher reached the conclusion that the value of citizenship can be enhanced through the interactive process of life in education in the form of dimensions such as: cognitive dimension, social dimension, skill dimension, and moral dimension.It is recommended to use modern media and methods to promote the spirit of citizenship, to celebrate national events, especially national day, to introduce children to their value and significance, to introduce children to their rights and duties and to affirm their right to social equality and equal opportunity.